Chapter 2 On the relationship between performance and intangible cultural heritage - McKerrell , Simon (Taylor & Francis, 2019)
This chapter deliberately ranges across disciplines because we wish to move towards a better understanding of the notion of performance in relation to ICH, where both terms are inherently transdisciplinary. We fi rst examine the concept of performance as it is understood in Theatre and Performance Studies, focussing on those aspects which are pertinent to ICH - embodiment, liminality and effi cacy. Second, we turn to Heritage Studies and outline how ideas of and about performance shape our understanding of heritage and its sociocultural dimensions. Thirdly, and fi nally, we investigate aspects of the tension between the performance of and the research on ICH through the lens of ethnomusicology, a discipline that is shaped by the tensions between the wealth of tacit cultural knowledge acquired by learning to perform works of ICH and the need to communicate such knowledge in research outputs.